Increasing the Competitiveness of the Economy is a Factor in Ensuring Economic Security - Saitmurod Alimbekovich, Djumanov; Dilshod Azimiddinovich, Sholdorov; Odiljon Egamberdi Ugli, Khudayberdiev; Rakhmonali Rasulovich, Obidov; Khabibullokh Ravshan Ugli, Razzokov (International Journal of Psychosocial Rehabilitation, 2020)
Increasing the competitiveness of the economy is one of the main social indicators of national as well as economic security. Therefore, during the period of independent development of the republic, great attention was paid to the implementation of reforms to improve the competitiveness of the economy and living standards. During the most difficult transition period of the country and society reform, strong social policy and the development of a unique, effective mechanism to increase the competitiveness of the economy have strengthened social stability and served to ensure economic security.